Status of mushroom production: global and national scenario - N. L. Devochkina; T. N. Surikhina; M. I. Ivanova (Овощи России, 2024)
Relevance. Mushroom farming has the potential to be a very profitable agribusiness venture that addresses several contemporary issues such as resource utilization, circular economy. Increasing mushroom production will increase its availability across the country, which will further help reduce food insecurity and also increase the income of small and marginal producers.Results. Mushrooms have enormous potential for medicinal and nutraceutical purposes. Over the past 20 years, global mushroom production has grown at a CAGR of 8.26%. This average annual growth rate is the highest for the Asian continent. Mainly six species of mushrooms dominate the global production and market, namely shiitake (26%), oyster mushroom (21%), black ear mushroom (21%), button mushroom (11%), flammulina (7%), straw mushroom (1%) and other types (13%). In the Russian Federation, industrial mushroom growing is actively developing. In recent years, 85 enterprises have been opened. The average annual growth rate of fresh mushroom production was 11.7%. Champignons and oyster mushrooms are mainly grown in Russia. Many obstacles faced by mushroom producers, including lack of technical knowledge, inadequate infrastructure, unorganized market, expensive inputs, etc., still need to be addressed through sufficient research and additional legislative solutions tailored to the requirements of Russian mushroom producers. Growing investments in smart automation to improve the efficiency and productivity of cultivated mushroom production involve advanced technologies such as robotics, artificial intelligence and the Internet of Things (IoT).